Keratinocyte differentiation factor 1 enhances cervical cancer cell viability and migration by activating the PI3K/AKT pathway - Chao Chen; Junhua Liao; Xingxing Sun (Journal of Obstetrics and Gynaecology)
Background The aim of This study is to investigate the effects of Keratinocyte differentiation factor 1 (KDF1) on cervical cancer cells and the underlying mechanisms.Methods The Gene Expression Profiling Interactive Analysis database was used to analyse KDF1 expression in cervical cancer and paracancerous tissue samples. The correlation between the expression of KDF1 and clinicopathological features was also analysed. Cervical cancer cells (HeLa cells) with KDF1 overexpression or knockdown were constructed. Reverse transcription polymerase chain reaction was used to detect the mRNA expression of KDF1 in cervical cancer tissues and cells. In different treatment groups of cervical cancer cells, protein expression of KDF1, cell viability, invasion, and migration were subsequently confirmed by western blotting, CCK-8 assay, transwell assay, and wound healing assay, respectively. A PI3K inhibitor (LY294002) was used to detect the effect of KDF1 on the phosphoinositide 3-kinase (PI3K)/Protein Kinase B (AKT) pathway.Results KDF1 was highly expressed in cervical cancer tissues and cell lines (p < 0.01), and was significantly associated with poor prognosis (p < 0.05). Knockdown of KDF1 in HeLa cells resulted in a significant decrease in cell proliferation, migration, and invasion, as well as phosphorylated PI3K (P-PI3K) and p-AKT levels (p < 0.01). However, KDF1 overexpression activated the PI3K/AKT pathway and significantly enhanced the malignant biological behaviour of cervical cancer cells (p < 0.01). Additionally, the PI3K inhibitor reduced the proliferation, invasion, and migration of HeLa cells overexpressing KDF1 (p < 0.01).Conclusion KDF1 enhances cervical cancer viability and migration by activating the PI3K/AKT pathway, and may serve as a therapeutic target for patients with cervical cancer.